Caging cationic polymer brush-coated plasmonic nanostructures for traceable selective antimicrobial activities - Ma, Jielin (2022)
Cationic polymers are under intense research to achieve prominent antimicrobial activity. However, the cellular and in vivo toxicity caused by nonspecific electrostatic interaction has become a major challenge for their practical applications. Here, the development of a "caging" strategy based on the use of a block copolymer consisting of a stealth block and an anionic block that undergoes degradation in presence of enzymes secreted by selective bacterial pathogens of interest is reported. The results have shown that antimicrobial cationic polymer brushes-coated gold nanorods (AuNRs) can be caged by the block polymer of poly(ethylene glycol) and anionic, lipase-degradable block of ε-caprolactone and methacrylic acid copolymer to afford neutrally charged surfaces. The caged AuNRs are activated by lipase released by bacteria of interest to endow an excellent bactericidal effect but show minimal binding and toxicity against mammalian cells and nonspecific bacteria that do not produce lipase. In this design, AuNRs play multifunctional roles as the scaffolds for polymer brushes, photothermal transducers, and imaging probes for traceable delivery of the activation and delivery of bactericidal cationic polymer brushes. The caging strategy opens new opportunities for the safe delivery of antimicrobial materials for the treatment of bacterial infections.